O processo de ensino e aprendizagem de noções matemáticas na Educação Infantil dos países fundadores do Mercosul: uma Revisão Sistemática da Literatura. - Warken, Clara Inês (2024)
In this paper, we present and discuss The process of teaching and learning mathematical notions in early childhood education in the founding countries of Mercosur: a Systematic Literature Review. This is a bibliographical and qualitative study, carried out in the field of Mathematics Education, to understand how the process of teaching and learning mathematical notions takes place in Early Childhood Education in the founding countries of the Southern Common Market (Mercosur), considering aspects highlighted in previous studies. Mercosur is an economic bloc founded by the countries of Argentina, Brazil, Paraguay, and Uruguay, whose educational systems have some differences in the way they work but are made up of the same levels of education: nursery, primary, secondary, and higher education, although under specific names. Early childhood education, the first stage of basic education, covers the period from birth to five years of age and is compulsory in the last year in all Mercosur member countries. In this stage, children construct/develop knowledge related to different areas of knowledge, especially mathematics, by approaching different mathematical concepts. In this sense, this research seeks to answer the following guiding question: In what aspects does the teaching and learning process of mathematical notions in early childhood education in the founding countries of Mercosur differ or converge, based on the research already carried out? To answer this question, we conducted a Systematic Literature Review (SLR) in the following databases: SciELO, SCOPUS, Google Scholar, Redalyc, LILACS, and Dialnet. At the end of the process, we found seventy-seven papers that were subjected to an interpretative analysis. The aspects revealed about the process of teaching and learning mathematical concepts in early childhood education, especially in the preschool phase in Argentina, Brazil, and Uruguay, were categorized according to the information about the teachers and their practices and the children and their experiences. The results show several similarities, including valuing children's experiences and daily lives, adapting teaching to their characteristics, promoting children's protagonism, using play, and centering teaching on the concept of numbers. The main differences lie in the focus of the work: the Argentinians emphasize practice with technology, the Brazilians value mathematical modeling, and the Uruguayans recognize the importance of family participation. In general, the use of games and play is a constant, and teachers are in the process of reflecting on their practices to improve the teaching of mathematical concepts and promote the integral development of children in different educational contexts.